Absolute BSD : the ultimate guide to free BSD - Lucas, Michael W. (Michael Warren), 1967- (No Starch Press, 2002)
This complete guide to FreeBSD includes coverage of installation, networking, add-on software, security, network services, system performance, kernel tweaking, filesystems, SCSI and RAID configurations, SMP, upgrading, monitoring, crash debugging, BSD in the office, and emulating other OSs.